Maternal-related factors associated with development and improvement of peripartum cardiomyopathy and therapeutic outcomes of bromocriptine - Pradnyaandara, I Gusti Bagus Mulia Agung; Mulyana, Ryan Saktika; Sutedja, Jane Carissa; Jagannatha, Gusti Ngurah Prana; Wibawa, I Bagus Satriya; Deantri, Fanny; Pradnyana, I Wayan Agus Surya; de Liyis, Bryan Gervais (Universitas Airlangga, 2024)
HIGHLIGHTS Younger age, black race, normotension, and multiparity indicate a poorer prognosis for peripartum cardiomyopathy recovery, while bromocriptine therapy reduces adverse events. ABSTRACT Objectives: This study aimed to fill the significant knowledge gap regarding peripartum cardiomyopathy (PPCM), a heart failure phenotype linked to pregnancy. The main objectives were to explore the factors influencing the development and progression of PPCM and to assess the outcomes of bromocriptine.Materials and Methods: Systematic search across PubMed, ScienceDirect, and Cochrane Library identified studies until December 2022. This study includes non-randomized prospective and retrospective studies, as well as relevant randomized controlled trials. Risk factors were compared between the recovered and non-recovered PPCM groups, and bromocriptine therapy outcomes were evaluated against standard heart failure treatment as the primary endpoint.Results: The analysis included 24 observational studies and 1 randomized controlled trial involving 1,651 PPCM patients; 9 studies evaluating the outcomes of bromocriptine therapy. The most prevalent factors were caesarean delivery (proportion=53%, 95%CI=41%-66%) and anemia (proportion=51%, 95%CI=38%-65%). Non-recovered patients were younger (MD=-1.04 years old, 95%CI=-1.82-(-0.27), p=0.008) and predominantly black (RR=1.82, 95%CI=1.43-2.31, p <0.001). Hypertensive disorders and primiparity were found less among non-recovered patients (RR=0.73, 95%CI=0.60-0.88, p=0.001; RR=0.81, 95%CI=0.66-0.99, p=0.04, respectively). Non-recovered patients also exhibited higher baseline serum creatinine levels, lower LVEF, larger left ventricular end-systolic diameter (LVESD), larger left ventricular end-diastolic diameter (LVEDD), and lower fractional shortening (all P-values<0.05). Furthermore, bromocriptine significantly reduced major adverse cardiac events (MACE), mortality, and increased LVEF (all P-values<0.05).Conclusion: Younger maternal age, black race, absence of hypertension, and multiparity are associated with poorer prognosis for PPCM recovery. Bromocriptine therapy demonstrates superior benefits in reducing adverse events in PPCM.